Addition of Electrophilic Radicals to 2‐Benzyloxyglycals: Synthesis and Functionalization of Fluorinated α‐C‐Glycosides and Derivatives. Issue 38 (16th August 2013) - Colombel, Sophie; Van Hijfte, Nathalie; Poisson, Thomas; Leclerc, Eric; Pannecoucke, Xavier
Abstract A new method for the synthesis of fluorinated α‐C‐glycosides is described. The reactions between highly electrophilic radicals (fluorinated or unfluorinated) and a 2‐benzyloxyglucal or galactal provide 2‐keto‐D‐arabino‐ or 2‐keto‐D‐lyxo‐hexopyranosides through an addition/fragmentation process. Sodium borohydride mediated or Meerwein–Ponndorf–Verley (MPV) reduction of these compounds provides α‐C‐glycosides that feature appropriate anchoring groups for further synthetic elaboration. The presence of CF2CO2iPr or CF2Br groups at the pseudo‐anomeric position allows efficient reduction/olefination or Br/Li‐exchange/nucleophilic‐addition sequences. These transformations open the way for the synthesis of fluorinated C‐glycosidic analogues of glycoconjugates.